Decisive how to make better choices in life and work - Heath, Chip. (New York Crown Business, 2013)
Just making a decision can be hard enough, but how do you begin to judge whether it's the right one? Chip and Dan Heath, authors of number one New York Times best seller Switch, show you how to overcome your brain's natural shortcomings.
Includes bibliographical references (pages [255]-256) and index.
Keywords: Decision making